Analysis of Monetary and Fiscal Policies on Economic Growth - Sihite, Lestari; Yosie Gabriela Panjaitan; Ayu Angelina Pasaribu; Sutejo Perangin Angin; Herry Daniel Laurent Marpaung (Efficient: Indonesian Journal of Development Economics, 2026)
This paper examines the effect of the combination of monetary and fiscal policies on economic growth in North Sumatera Province using time series data for the period 2010-2024. The analysis was conducted using VAR method and forecasting. The result show that local government spending and Local Own-Source Revenue contribute positively and significantly to economic growth. Conversely, inflation has a negative and significant impact on economic growth. These findings confirm that local fiscal instruments are the main drivers of the economy. On the other hand, General Allocation Funds and the BI Rate are not proven to have a significant effect on economic growth. No flypaper effect was found, because Local Own-Source Revenue plays a greater role in driving RGDP than General Allocation Funds, indicating that North Sumatra's economic performance is more supported by its internal potential. For the Policy Mix, a combination of expansive and productive fiscal policies with stable and accommodative monetary policies is most effective. While local governments support growth, BI stabilizes and provides a favorable economic environment.